2020
DOI: 10.1016/j.cej.2019.04.041
|View full text |Cite
|
Sign up to set email alerts
|

Hydrodynamics and gas-liquid mass transfer around a confined sliding bubble

Abstract: An experimental investigation of gas-liquid mass transfer in the wake of a confined air bubble sliding under an inclined wall in a 2D Hele-Shaw cell is reported. A colorimetric technique based on an oxygen-sensitive dye was used to visualize the oxygen transfer. Bubble velocities, shape eccentricities, interfacial areas and, for the first time, the instantaneous spatio-temporal distribution of oxygen concentration fields in the bubble wake, have been investigated for upper wall inclination angles of 10° ≤ α ≤ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 35 publications
(76 reference statements)
1
8
0
1
Order By: Relevance
“…In keeping with this context, the present work reports investigations on the gas-liquid mass transfer process around Taylor bubbles flowing in the same long, in-plane, spiral-shaped milli-reactor as the one used in . The resazurin-based colorimetric method described by Dietrich and Hebrard (2018); Dietrich et al ( , 2019, Kherbeche et al (2019Kherbeche et al ( , 2013 and Liu et al (2020) is implemented to measure the equivalent oxygen concentration fields inside the liquid slugs throughout the 3 m long tube. Two different configurations, in which the tube curvature changes continuously, are considered in order to cover a larger range of cur-vature ratios (i.e., Dean numbers).…”
mentioning
confidence: 99%
“…In keeping with this context, the present work reports investigations on the gas-liquid mass transfer process around Taylor bubbles flowing in the same long, in-plane, spiral-shaped milli-reactor as the one used in . The resazurin-based colorimetric method described by Dietrich and Hebrard (2018); Dietrich et al ( , 2019, Kherbeche et al (2019Kherbeche et al ( , 2013 and Liu et al (2020) is implemented to measure the equivalent oxygen concentration fields inside the liquid slugs throughout the 3 m long tube. Two different configurations, in which the tube curvature changes continuously, are considered in order to cover a larger range of cur-vature ratios (i.e., Dean numbers).…”
mentioning
confidence: 99%
“…Note : Calibration curve must be monotonic in order to make quantitative calculation, but it may not be linear, depending on the superposition of mass transfer information within and outside of the focus planes [11] and dye concentration [27] .…”
Section: Resultsmentioning
confidence: 99%
“…As for the non-invasive and instantaneous advantages, Yang et al [46] further investigated the mass transfer contribution of the bubble formation stage to the overall process. The liquid side mass transfer coefficients at the moment immediately after the pinch-off stage were obtained and founded bigger than in the flowing stage, which demonstrated that the contribution of the bubble formation stage to overall mass transfer was reasonably large [47,48]. Furthermore, Yang et al [49] studied the mass transfer intensification in a square meandering channel.…”
Section: Application Of the Visualization Techniques To Gas-liquid Systemsmentioning
confidence: 96%